Late onset sepsis: comparison between coagulase-negative staphylococci and other bacteria in the neonatal intensive care unit. Issue 10 (3rd October 2018) - Berlak, Neta; Shany, Eilon; Ben-Shimol, Shalom; Chertok, Ilana Azulay; Goldinger, Gil; Greenberg, David; Melamed, Rimma
Abstract: Objective: To compare demographic and clinical features of neonates with late-onset sepsis due to coagulase-negative-staphylococcus with those due to other bacterial pathogens. Study design: Retrospective, population-based cohort study. Data on infants less than 90 days old diagnosed with late-onset bacterial sepsis in the neonatal intensive care unit were reviewed. Univariable and multivariable analysis were performed. Results: Two hundred and sixteen sepsis episodes were identified: coagulase-negative-staphylococcus caused 113 (52.3%) and other pathogen 103 (47.7%). Patients with coagulase-negative-staphylococcus sepsis had lower gestational age and younger age at onset, higher rates of parenteral nutrition exposure and normal temperature, lower rates of necrotizing enterocolitis, meningitis and neutropenia than patients with sepsis caused by other pathogens. In multivariable analysis, parenteral nutrition was the only independent risk factor for coagulase-negative-staphylococcus sepsis (odds ratio: 3.5, 95% confidence interval: 1.4–8.6). Conclusions: Initial empiric treatment for suspected sepsis should be targeted for other pathogens than coagulase-negative-staphylococci and vancomycin treatment should be reserved for infants with specific risk factors and according to local antimicrobial susceptibility.